The comparative analysis of english and lithuanian terms of transport engineering - Marina, Valerija (Transport, 2003)
The article presents the analysis of transport terms contained in the English – Lithuanian Dictionary of Automobile Transport and special texts. English terms are compared with their Lithuanian equivalents from the perspective of the theory of language relativity to identify universal and different patterns of expressing the same reality. All terms are classified into various groups according to this principle. It is also shown that an object expressed in Lithuanian by a single word may be denoted by multiple English words. Problems arising due to different approaches of speakers of different languages to objects of reality in giving names and classifying them are identified and some recommendations for their solution are given.First Published Online: 19 Dec 2011